Hambatan dalam upaya pengembangan BIPA di luar negeri - Nastiti, Ayu Dwi; Datil, Lale Li; Sukma, Bayu Permana (Badan Pengembangan Bahasa dan Perbukuan, 2019)
Law Number 24 Year 2009 gives a mandate to National Agency of Language Cultivation and Development, Ministry of Education and Culture through the Centre for Language Strategy and Diplomacy Development to increase function of Indonesian language as an international language. Themandateisthenrealizedbythe Centre by launching a program deploying Indonesian language teachers to 23 countries. As part of its evaluation, this research aims to identify obstacles in developing Indonesian as a Foreign Language (IFL) abroad particularly during the program from 2015 to 2017. This research used a descriptive qualitative method through document analysis.The data wereobtainedfrom95 assignment reports by the Indonesian as a Foreign Language (IFL) teachers assigned by the Centre for Language Strategy and Diplomacy Development. The results show that there are eight aspects of obstacles found. The aspects are learning standard, students, teachers, infrastructures, institutions, environments, administration abroad, and inter-agency coordination.